Neofunctionalization of Glycolytic Enzymes: An Evolutionary Route to Plant Parasitism in the Oomycete Phytophthora nicotianae - Marie-Line Kuhn; Jo-Yanne Le Berre; Naima Kebdani-Minet; Franck Panabières (Microorganisms, 2022)
Oomycetes, of the genus Phytophthora, comprise of some of the most devastating plant pathogens. Parasitism of Phytophthora results from evolution from an autotrophic ancestor and adaptation to a wide range of environments, involving metabolic adaptation. Sequence mining showed that Phytophthora spp. display an unusual repertoire of glycolytic enzymes, made of multigene families and enzyme replacements. To investigate the impact of these gene duplications on the biology of Phytophthora and, eventually, identify novel functions associated to gene expansion, we focused our study on the first glycolytic step on P. nicotianae, a broad host range pathogen. We reveal that this step is committed by a set of three glucokinase types that differ by their structure, enzymatic properties, and evolutionary histories. In addition, they are expressed differentially during the P. nicotianae life cycle, including plant infection. Last, we show that there is a strong association between the expression of a glucokinase member in planta and extent of plant infection. Together, these results suggest that metabolic adaptation is a component of the processes underlying evolution of parasitism in Phytophthora, which may possibly involve the neofunctionalization of metabolic enzymes.